RELEVANSI WAKAF TERHADAP TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGS) DALAM PERSPEKTIF MAQĀṢID AL-SHARĪ‘AH - Wakil, Abdul (Finance : Journal of Accounting and Finance, 2023)
This paper aims to provide an overview of the potential strategic role of waqf in the context of global development, particularly in supporting the achievement of the Sustainable Development Goals (SDGs). The main focus of this study is to build a conceptual framework that demonstrates the convergence between waqf principles and the core objectives of the SDGs, which are also in line with the maqāṣid al-sharī‘ah. This research adopts a qualitative approach using literature review methods, based on systematically analyzed secondary data. The analysis explores relevant scholarly literature to understand the potential integration of waqf within the sustainable development framework. The study finds that the majority of the 17 SDGs align significantly with the long-term objectives of Islamic law. This opens up considerable opportunities for waqf stakeholders to develop waqf-based development programs that are consistent with the SDGs framework. Furthermore, the research reveals that global waqf assets possess substantial financial capacity to assist Muslim-majority countries in timely and effectively realizing the most relevant and urgent SDG targets. The scope of this study is limited to analyzing the potential role of waqf in supporting SDG goals that are aligned with the maqāṣid al-sharī‘ah. To maintain a coherent focus, the study does not compare waqf with other forms of Islamic philanthropy or social finance instruments in achieving similar objectives. The findings of this research offer a conceptual framework for implementing waqf-based development that is oriented toward the maqāṣid al-sharī‘ah. In addition, the paper presents several practical and strategic recommendations for waqf administrators and Islamic philanthropic institutions to take an active role as catalysts in development initiatives aligned with the SDGs. This paper provides an original contribution to the existing literature by specifically examining the role of waqf in supporting the most urgent SDG agenda items based on the maqāṣid al-sharī‘ah. As such, this study fills a research gap by systematically exploring the potential collaboration between the global waqf system and the sustainable development agenda.